Teori Pragmatika Bahasa dan Kesantunan Berbahasa - Nuraini Kumala Suri; Silvina Noviyanti; Anggia Tri Agustina (Journal on Education, 2025)
This research uses library research methods. The application of this method is carried out systematically through several steps, starting from determining a general topic, careful literature analysis, collecting and analyzing books as a theoretical basis, as well as searching for journals and relevant literature from previous research regarding language pragmatics and language politeness. The purpose of writing this article is to understand the theory of language pragmatics and language politeness. This article discusses the history of pragmatics, the definition of pragmatics, factors that cause impolite language use, politeness in language, and politeness strategies in language.